Optimization of Laccase Enzyme Pretreatment Process Parameters of Empty Fruit Bunches (EFB) Using One-Factor-At-a-Time (OFAT) - Ishmael, Ukaegbu Chinonso; Rashid, Shah Samiur; Nik Sharifah Suhaiza, Nik Wan Ahmad (Universiti Malaysia Pahang, 2016)
Global warming due to increasing in carbon dioxide emission worldwide is generating much concern recently. The unsustainability of mans' activity in the generation of energy is a major cause of these changes in the environment. Production of energy carriers from petroleum and the fossil is a major contributor to challenges currently experienced in the world today. Sustainable biofuel from lignocellulosic biomass ensures sustainability of all processes of production. However, alternative sources of energy have been developed and green energy from lignocellulose biomaterials proved to be the ultimate alternative. Conversely, production of biofuels such as bioethanol from biomass needs pretreatment of the biomass for efficient saccharification of the sugar content of the biomass. Pretreatment has been conventionally done with chemicals such as sulphuric acid or sodium hydroxide but a critical review of these pretreatment process showed that the problem of greenhouse gas emission and generation of inhibitory substances such as furfural and hydroxyl methyl furfural still exists. In other to produce biofuels in a sustainable and environmental friendly way, this study adopted laccase enzyme for the pretreatment of empty fruit bunches (EFB). The degree of delignification after pretreatment of the EFB was assessed directly by the percentage of the pre-pretreatment weight lost after pretreatment, and also indirectly through the saccharification of the pretreated biomass with cellulase enzyme to check the quantity of sugar produced by altering pretreatment process parameters. Pretreatment parameters such as pretreatment time, temperature, enzyme and substrate concentrations, pH, and substrate size were studied using OFAT design. Results showed sample size of 2 mm, temperature at 35 oC, time of 4 h, substrate concentration of 5 % (w/v), pH 5 and enzyme concentration of 20 IU/g of EFB as optimized pretreatment process conditions. Room temperature (25 ± 3 °C) could also be used during the pretreatment process based on the fact that similar results were obtained when pretreatment was done at room temperature and 35 oC.